Carbonaceous matter in the atmosphere and glaciers of the Himalayas and the Tibetan plateau: An investigative review. (January 2021) - Li, Chaoliu; Yan, Fangping; Kang, Shichang; Yan, Caiqing; Hu, Zhaofu; Chen, Pengfei; Gao, Shaopeng; Zhang, Chao; He, Cenlin; Kaspari, Susan; Stubbins, Aron
Highlights: Characteristics of carbonaceous matter in the HTP are reviewed. A synthesis of published HTP carbonaceous matter data is provided. Future directions for HTP carbonaceous matter research are suggested. Abstract: Carbonaceous matter, including organic carbon (OC) and black carbon (BC), is an important climate forcing agent and contributes to glacier retreat in the Himalayas and the Tibetan Plateau (HTP). The HTP – the so-called "Third Pole" – contains the most extensive glacial area outside of the polar regions. Considerable research on carbonaceous matter in the HTP has been conducted, although this research has been challenging due to the complex terrain and strong spatiotemporal heterogeneity of carbonaceous matter in the HTP. A comprehensive investigation of published atmospheric and snow data for HTP carbonaceous matter concentration, deposition and light absorption is presented, including how these factors vary with time and other parameters. Carbonaceous matter concentrations in the atmosphere and glaciers of the HTP are found to be low. Analysis of water-insoluable organic carbon and BC from snowpits reveals that concentrations of OC and BC in the atmosphere and glacier samples in arid regions of the HTP may be overestimated due to contributions from inorganic carbon in mineral dust. Due to the remote nature of the HTP, carbonaceous matter found in the HTP has generally been transported from outside the HTP (e.g., South Asia), although local HTP emissions may also be important at some sites. This review provides essential data and a synthesis of current thinking for studies on atmospheric transport modeling and radiative forcing of carbonaceous matter in the HTP.